Genomic analysis of methicillin-resistant Staphylococcus aureus strain SO-1977 from Sudan - Ali, Mohamed S.; M. Isa, Nurulfiza; Abedelrhman, Faisal M.; Alyas, Tahani B.; Mohammed, Sara E.; Ahmed, Abdallah E.; Ahmed, Zainab S. A.; Lau, Nyok-Sean; Garbi, Mohamed I.; Abdullah, Amirul Al-Ashraf; Seed, Almeen O.; Omer, Rihab A.; et al. (BioMed Central, 2019)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is known as a leading cause of morbidity and mortality. Investigation of the MRSA’s virulence and resistance mechanisms is a continuing concern toward controlling such burdens through using high throughput whole Genome Sequencing (WGS) and molecular diagnostic assays. The objective of the present study is to perform whole-genome sequencing of MRSA isolated from Sudan using Illumina Next Generation Sequencing (NGS) platform.